Analysis of High School Students' Difficulties in the Material of Two Variable Linear Equation Systems - Wahyuni, Septia; Noviani, Julia; Ismayanti; Saputra, Edy (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2023)
Some students still find it difficult to learn mathematics because of the many obstacles they face. The view that mathematics is an abstract, theoretical science, has symbols and formulas that are difficult and confusing so that students have difficulty understanding it. This study used qualitative research methods. Research subjects were taken using a purposive sampling technique. Researchers then grouped students based on their level of ability, namely high ability, medium ability and low ability. The research subjects in this study were 3 students. The data collection technique in this study used a test technique which contained a system of two-variable linear equations and interviews. Data analysis techniques are data reduction, data presentation and drawing conclusions. Based on the research results obtained in solving problems on the material system of linear equations of two variables, it was concluded that there were several difficulties experienced by students, namely conceptual difficulties which lay in the fact that students were unable to deduce information from a given concept, then principle difficulties, namely difficulties applying solving methods in solving problems, and skill difficulties that lie in the difficulty of arithmetic operations.